(untitled) (Journal of International Studies, 2020)
Relations between the Middle East and Southeast Asia have for many centuries been described as an one-sided relationship where the scriptural and religion-wise dominant Middle East has "enlightened" the "syncretistic" Southeast Asia with its oral and lax Sufi and HinduBuddhist traditions. Southeast Asian students studying in Cairo have enforced this perception since the 19th century - the Islamic resurgence of the 1980s was the last one to import perceived "Arab" ideas across the continent and into the "Lands behind the Wind". However, recently there has been a tremendous change in this relationship, where modernizing discourses on Islam and numerous trade initiatives of the "Asian Tiger States" like Malaysia and Singapore have started to influence and even dominate emerging dialogues with rather stagnant Middle Eastern partners. Knowledge on Islamic banking, on halal food trading